In Silico Analysis of Imidazole Derivatives Targeting Estrogen Receptor Alpha as Anti-Breast Cancer Candidates - Atika Suri; Okta Suryani (KOVALEN: Jurnal Riset Kimia, 2026)
Breast cancer is one of the leading causes of mortality among women worldwide and is frequently associated with the overexpression of Estrogen Receptor alpha (ERalpha). This study aimed to evaluate the potential of imidazole derivatives as anticancer candidates targeting ERalpha (PDB ID: 3ERT) using an In Silico approach. Ten imidazole derivatives were analyzed through Lipinski’s Rule of Five screening, ADMET prediction, and molecular docking studies, with 4-hydroxytamoxifen employed as the positive control. Lipinski screening indicated that all compounds met the drug-likeness criteria. ADMET prediction revealed that most compounds exhibited good intestinal absorption (HIA > 85%) and adequate Caco-2 permeability, with no predicted hepatotoxicity. Molecular docking results showed that all compounds had RMSD values below 2angstroms, indicating stable interactions with the receptor. Among the tested compounds, 1-(2-Phenyl-2-propoxyethyl)-1H-imidazole demonstrated the best binding affinity (-6.3103 kcal/mol) among the imidazole derivatives; however, this value remained lower than that of the positive control, 4-hydroxytamoxifen (-8.6492 kcal/mol), which served as the primary benchmark for binding affinity comparison. Ligand–receptor interactions involved key amino acid residues within the active site of the 3ERT protein. Based on these findings, 1-(2-Phenyl-2-propoxyethyl)-1H-imidazole (compound 9) shows potential as a promising breast anticancer candidate and is recommended for further investigation through In vitro and in vivo experiments are required to verify its biological activity and evaluate its safety profile.